An Automated Medical Support System based on Medical Palmistry and Nail Color Analysis (International Journal of Engineering and Computer Science, 2018)
In an Automated Medical Palmistry System (AMPS) as an application of digital image processing and analysis technique can be useful in healthcare domain to predict diseases for human being. The proposed work is based on design and implementation of an automated system to detect various health conditions of patients. The images of human palm and nails will be the input to the system.  By applying digital image processing techniques on input images, certain features in the image will be identified. The knowledge base of medical palmistry will be used to analyze certain features in images and prediction probable disease.